Ontogeny of swimming behaviour of two temperate clingfishes, Lepadogaster lepadogaster and L-purpurea (Gobiesocidae) - Faria, Ana M. (2018)
Gobiesocids are typically reef-dwelling species whose larvae have been found in several nearshore rocky environments; this suggests a possible retention pattern for these species. Retention may occur due to the physical features of an area and/or active larval behaviour, such as swimming abilities. In the laboratory, we measured the ontogeny of swimming behaviour (routine speed and critical speed, U-crit) of 2 clingfish species, Lepadogaster lepadogaster and L. purpurea. L. lepadogaster larvae swam better than L. purpurea larvae, but this difference might be related to differences in water temperature, since the former is a spring spawner, whereas the latter spawns during winter. It is well known that water viscosity increases with decreasing temperature, making swimming more difficult. Routine and critical swimming speeds of larvae of both species increased with ontogeny (size) despite high variability at any ontogenetic state. U-crit ranged from 1 to 9.4 and 1.2 to 6.5 cm s(-1) in L. lepadogaster and L. purpurea, respectively. Routine speeds were similar to 18 to 19% of the maximum U-crit registered for both species. Interestingly, swimming speed started to decrease as settlement size (10 to 11 mm total length) was approached, concurrent with the development of a ventral sucking disk that allows individuals to attach to the bottom of the swimming chamber and counteract strong currents. This shift in swimming behaviour that is associated with settlement is probably an adaptation to the cryptobenthic mode of life of these fish.